Stress Signaling in the Methionine-Choline-Deficient Model of Murine Fatty Liver Disease - Soon, Russell K. (2010)
BACKGROUND & AIMS: Stress signaling, both within and outside the endoplasmic reticulum, has been linked to metabolic dysregulation and hepatic steatosis. Methionine-choline-deficient (MCD) diets cause severe fatty liver disease and have the potential to cause many types of cellular stress. The purpose of this study was to characterize hepatic stress in MCD-fed mice and explore the relationship between MCD-mediated stress and liver injury. METHODS: Stress signaling was examined in mice fed MCD formulas for 4–21 days. Signaling was also evaluated in mice fed MCD formulas supplemented with clofibrate, which inhibits hepatic triglyceride accumulation. The role of the pro-apoptotic stress protein C/EBP homologous protein (CHOP) in MCD-mediated liver injury was assessed by comparing the responses of wild-type and CHOP-deficient mice to an MCD diet. RESULTS: MCD feeding caused steatohepatitis coincident with the activation of cJun N-terminal kinase and caspase-12. In contrast, MCD feeding did not activate inositol-requiring protein-1 and actually suppressed the expression of X-box protein-1s. MCD feeding caused weak stimulation of PKR-like ER-resident kinase, but robust activation of general control non-derepressible-2, followed by the phosphorylation of eukaryotic initiating factor-2α and induction of CHOP. Clofibrate eliminated MCD-mediated hepatic steatosis but did not inhibit diet-induced stress. CHOP deficiency did not alleviate, and in fact worsened, MCD-mediated liver disease. CONCLUSIONS: MCD feeding causes an integrated stress response in the liver rather than a classical unfolded protein response. This stress response does not by itself lead to liver injury. CHOP, despite its identity as a mediator of stress-related cell death, does not play a central role in the pathogenesis of MCD-mediated liver disease.